PEMBUATAN KOMPOS DARI CAMPURAN 60% BERAT TANDAN KOSONG KELAPA SAWIT DAN 40% BERAT AZOLLA MICROPHYLLA DENGAN BANTUAN PUPUK CAIR ORGANIK AKTIF - Andry Hammonang Sianturi, Immanuel Putra Riau Hutagaol, Bambang Trisakti, Irvan (Jurnal Teknik Kimia USU, 2019)
The process of composting empty fruit bunches and Azolla microphylla by asistance active organic liquid fertilizer was an alternative in the utilization of solid waste produced from the palm oil mill. This research was to produce good quality compost from a mixture of 60%:40% weight empty fruit bunches and azolla microphylla with asistance active organic liquid fertilizer. The composting process is done by entering empty fruit bunches and Azolla microphylla on the composter and added active organic liquid fertilizer to achieve the moisture content  value of 55%-65%. During composting, the moisture content was kept on the optimum condition by adding the active organic liquid fertilizer. The parameters analyzed were temperature, moisture content, pH, water holding capacity, electrical conductivity, and C-N. The result showed that compost can be produced within ± 30 days with characteristic of pH 8.8; Moisture Content 59,92%, Water Holding Capacity 86%,  C 27.24%,  N 1.53 % and C/N 17.80%